Design and Optimization of Self‐Isolation GaN HEMT with Lateral‐Polarity‐Structure. Issue 4 (4th January 2023) - Dai, Yijun; Zhao, Zihui; Luo, Tian; Yu, Zhehan; Chen, Li; Guo, Wei; Ye, Jichun
Abstract : Herein, polarization‐induced self‐isolation free from process damages in AlGaN/GaN high‐electron‐mobility transistor (HEMT) by the incorporation of lateral‐polarity structure (LPS) is demonstrated. The incorporation of LPS into the AlGaN/GaN heterojunction shows that 2D electron gas (2DEG) is formed in the III‐polar heterojunction but depleted in the N‐polar counterpart. A large lateral barrier height of 3.5 eV between the III‐polar and N‐polar domain boundary is revealed and buffer leakage is proved to be responsible for the weakened isolation characteristics. To suppress the buffer leakage, the influence of the AlGaN buffer on the leakage current is comprehensively investigated. Compared to pure GaN film and AlGaN/GaN heterojunction, two‐terminal isolation leakage current in AlGaN/GaN/Al0.2 Ga0.8 N heterojunction is greatly reduced by about nine orders of magnitude to as low as 10 −11  A as experimentally confirmed. The incorporation of LPS into AlGaN/GaN heterojunction provides a novel planar isolation technique with excellent device performance by eliminating the isolation leakage path. Abstract : The correlation between the isolation leakage current at 10 V and doping concentration is demonstrated. Buffer leakage is the dominant factor when the Al content is below 5%, while the isolation leakage current drops significantly and becomes irrelevant to doping concentration when the Al content is 20% and above.